Disrupting the Islamic Legal Judiciary Regarding Theft and Drinking Alcohol and Its Impact on Society, a Jurisprudential Study Comparing Sharia and Law - Zobaei , Shkor Mahmoud Farhan Al (International Journal of Psychosocial Rehabilitation, 2020)
The judiciary is a trust that needs to be done to the fullest. That litigation must be in accordance with what God Almighty has prescribed because preserving souls, symptoms, and money can only be by standing at the limits of the law. The Prophet, may God’s prayers and peace be upon him, has begun judging himself and has not feared blame in God. The judiciary is not subject to the authority of a ruler nor to his desires, for he derives his power from the authority of God Almighty, so he does not politicize, and there is no favoritism towards anyone. Judge: He is categorical of matters that are tightly controlled by her, and he is the one who decides between people by virtue of Sharia. The judge appointed the necessity to establish the imposition: This is because the Grand Imam's monument was imposed without controversy between the people of truth. The meaning of the judiciary is to clarify the legal ruling, compel it, and separate the disputes. Elimination has multiple meanings - creation, separation, cutting, emptiness, matter. The difference between the judiciary and the fatwa, as the fatwa is a statement of judgment without binding. As for the judiciary: it is obligating the opponent to rule. The ruler on the one hand is proof, he is a witness, and on the one hand the command and the prohibition he is a mufti, and on the one hand the obligation to do so, he has authority. Whoever leads the judiciary must be: sane, adult, Muslim, free, visionary, speaking, safe from the point of slander, male, diligent, just. It is permissible for a non-Muslim to take the charge of eliminating the people of his religion only, upon tap. Theft: is the taking of a rational adult, chosen and committed to the rule of Islam, a quorum of money with the intent to steal from a score similar to him, which has no suspicion.